Develop a Sensor System to Calculate the Mutual Pressure Between the Socket and Limb in Amputation above the Knee - Raed Najjar; Yara Mohammad; Ghader Ali (Tishreen University, 2019)
This research aims to develop a system of thin slice sensors that rely on the principle of variable electrical resistors and invested in the calculation of the mutual pressure between the socket and limb prosthesis from above the knee because this pressure is important in determining the efficiency of the prosthesis as the quality of the prosthesis depends on The quality of the socket and the quality of the socket in turn are linked to the optimal distribution of pressure on loadable and non-loadable areas. In five cases of prosthesis alignment through the angle between the knee axis and the socket axis, pressure was calculated for an amputee above the knee at the age of 35 years. The patient was satisfied and it was found that the most suitable angle or the studied condition ranged between 14 - 16 degrees in the front direction corresponding to the direction of normal walking يهدف هذا البحث إلى تطوير نظام من الحساسات الشرائحية الرقيقة التي تعتمد على مبدأ المقاومات الكهربائية المتغيرة و استثمارها في حساب الضغط المتبادل بين الجذمور و قميص طرف صناعي من ما فوق الركبة لما لهذا الضغط من أهمية في تحديد كفاءة الطرف الصناعي حيث أن جودة الطرف الصناعي تتوقف على جودة القميص و جودة القميص بدورها ترتبط بالتوزع الأمثل للضغط على المناطق القابلة للتحميل و المناطق غير القابلة للتحميل .تم حساب الضغط لمصاب بالبتر من ما فوق الركبة يبلغ من العمر 35 عاماً و ذلك في خمس حالات لتسامت الطرف الصناعي من خلال الزاوية بين محور الركبة الصناعية و محور القميص, تم وضع معايير لتقيم كفاءة القميص و زوايا التسامت المثالية بالاعتماد على نظام الحساسات و التجربة و رضى المصاب و تبين أن زاواية التسامت المثالية للحالة المدروسة تراوحت بين 14 - 16 درجة في الاتجاه الأمامي الموافق لاتجاه المشي الطبيعي .